HUBUNGAN GAYA BELAJAR DAN SIKAP TERHADAP MATA PELAJARAN MATEMATIKA DENGAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 2 PAGAR ALAM - Tri Idaliyah (UNIB Press, 2021)
This study aims to analyze the the correlation among learning styles, attitudes toward mathematics and mathematics learning achievements of the eighth grade students of SMP Negeri 2 Pagar Alam. This research is a quantitative study with a correlational method. The population of this study were students of class VIII SMP Negeri 2 Pagar Alam, through proportional stratified random sampling. The research instrument used in the form of a learning style questionnaire, attitude questionnaire towards Mathematics subjects and documentation of student learning achievement. The data analysis technique used to test the correlation between variables X1 to Y and X2 to Y is partial correlation analysis, to test the correlation of X1, X2 to Y, multiple regression analysis is used. The results showed that there was a significant relationship between learning styles and attitudes towards mathematics subjects simultaneously on mathematics learning achievement. A significance score of 0.016 is lower than 0.05. This means that Ha is accepted, while Ho is rejected, so it can be concluded that the right learning style will improve students' Mathematics learning achievement followed by high attitudes towards Mathematics subjects. The more precise the student's learning style that is applied plus a positive attitude towards Mathematics subjects, the more optimal the Mathematics learning achievement will be